MODEL OF POOR SOCIETY EMPOWERMENT THROUGH OPTIMIZING THE POTENTIAL OF ZAKAT: A Case Study in Lampung Province - Hayati, Keumala; Caniago, Indra (Journal of Indonesian Economy and Business, 2012)
Previous research found a large zakat potential in Lampung province that reached Rp 644 billion (opinion 2 percent from GDRP) and Rp1.3 trillions (opinion 4.3 percent fromGDRP). This potential could assist the government in tackling poverty. Based on this potential, further research was to design Model of Poor Empowerment through Optimizingthe Potential of Zakat. The method used is a case study. There were five propositions developed, namely: (1) Optimization of the collection of zakat requires synergy role between LAZ/BAZIS (Zakat Executor Institution), government and society, (2) Empowerment Program of the poor through productive zakat by LAZ could be done by using Community-Based Development, (3) the distribution of zakat in the effort of empowering the poor requires synergy programs between LAZ and the government, (4) the appropriate organizational structure of LAZ is Geographic structure, and (5) Management of collection and distribution of zakat depends on a reliable information system.The result shows that the role of government is as obligatory zakat regulator either to individuals, companies, and government agencies. Furthermore, Muzakki consisting of individuals, corporations and government agencies collected their zakat to LAZ/BAZIS. In the case of zakat distribution, government and LAZ should work together so the governments poverty reduction programs and LAZ empowerment of the poor program will be mutually synergistic and will not overlap each other. LAZ could also run the program of the Community-Based Development. The study also found LAZ should use geographical organizational structure. This structure allows the formation of decentralized LAZ regency/city. Further LAZ works need the support of a reliable information system.Keywords: Empowerment of the poor, zakat potential, synergy between government and LAZ poverty reduction program, Community Based Development.